Mechanical Structure Optimization of Sewerage Inspection Robot - Tan, CheeFai; Lim, T.L. (Praise Worthy Prize, 2012)
The sewerage inspection robot is a distance controllable robot by a human operator during the sewerage pipe inspection operation. It travel on wheels and is composed of mechanism like a mobile robot. The concept of this inspection robot is used to inspect the sewerage pipe that is not accessible and hazardous for human. The sewerage inspection robot will detect and inform the defect location for any maintenance and repair works. The common problems in the sewerage pipe are breakage, crack and obstacles between the connections. The developed sewerage inspection robot needs to be designed to withstand the collapse of the sewerage pipe so that the robot is fit to be used for next jobs. The project presents the mechanical structure optimization of sewerage inspection robot. The robot is solid rectangular shape and a designed for sewerage pipe. The paper also focused on the structural analysis of the developed robot.